(untitled) (Future Cities and Environment, 2025)
This article aims to take a cross-sectional look at what may be some of the urban planning strategies that allow us to deal with the sustainable future of our territories, relying on the necessary link between the two main realities where we live, and which are apparently anthagonic: the Urban and the Rural Worlds. To do this, this study is structured in a series of sections that address the subject from different perspectives, but respond to a common argument discourse that allows them to be put in mutual relationship. From this perspective, some preliminary questions are introduced that must be taken into account in the study of the urban-rural relationships, to then identify the most important work topics. The scenario study has helped to develop a methodological and strategic discourse that can contribute to the improvement of these relationships, and the paper finishes with some conclusions of the study. This document seeks to provide some reflections and tools that can help to address the problem of our cities and our territories in the search for a better quality of life.